Elly's Reader: learning through mobile apps / Nur Hidayah Fauzi ... [et al.] - Fauzi, Nur Hidayah; Wan Mohammad, Wan Anisha; Johan, Elly Johana; Mohd Mydin, Azlina; Mohamed Yusoff, Syarifah Adilah (Unit Penerbitan JSKM, 2023)
Education and the learning process are very important. In the current era of technology, everything related to education and the learning process such as e-learning is also at the fingertips. Since early literacy and resources to help kindergarten children learn to read are limited, quite boring, ineffective, and still go through the traditional method, Elly's Reader is being developed to overcome these problems. Elly's Reader is a learning mobile application to help kindergarten students to read anywhere at any time effectively and quickly. The scope of the project is children from Tabika Kemas Kampung Kota Bukit. Surveys and the requirements needed are identified before the application is implemented to make sure that the functionality and usability of the application are applied. ADDIE Model is used in the development of Elly's Reader. The main purpose of Elly's Reader is to facilitate the process of teaching and learning not just to the students but also to the teachers and parents. By using Elly's Reader, children, teachers, and parents can handle the learning process effectively, quickly, and smoothly with a more enjoyable learning method.